Interactions between PAMAM dendrimers and DOPC lipid multilayers: Membrane thinning and structural disorder - Fox, Laura J.; Slastanova, Anna; Taylor, Nicolas; Wlodek, Magdalena; Bikondoa, Oier; Richardson, Robert M.; Briscoe, Wuge H. (Biochimica et biophysica acta. General subjects, 2021)
Understanding the structure of hybrid nanoparticle-lipid multilayers is of fundamental importance to their bioanalytical applications and nanotoxicity, where nanoparticle-membrane interactions play an important role. Poly(amidoamine) (PAMAM) dendrimers are branched polymeric nanoparticles with potential biomedical applications due to precise tunability of their physicochemical properties. Here, the effect of PAMAM dendrimers (2.9–4.5 nm) with either a hydrophilic amine (NH2) or a hydrophobic C12 chain surface termination on the 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) multilayers has been studied for the first time. DOPC multilayers were created by the liposome-rupture method via drop-casting dendrimer-liposome dispersions with the dendrimers added at different concentrations and at three different stages. The multilayer structure was evaluated via the analysis of the synchrotron X-ray reflectivity (XRR) curves, obtaining the bilayer d-spacing, the coherence length from the Scherrer (Ls) analysis of the Bragg peaks, and the paracrystalline disorder parameter (g). Dendrimer addition led to lipid bilayer thinning and more disordered multilayer structures. Larger hydrophobic dendrimers caused greater structural disruption to the multilayers compared to the smaller dendrimers. The smallest, positively charged dendrimers at their highest concentration caused the most pronounced bilayer thinning. The dendrimer-liposome mixing method also affected the multilayer structure due to different dendrimer aggregation involved. These results show the complexity of the effect of dendrimer physicochemical properties and the addition method of dendrimers on the structure of mixed dendrimer-DOPC multilayers. These insights are useful for fundamental understanding of nanotoxicity and future biomedical application of nanocomposite multilayer materials in which nanoparticles are added for enhanced properties and functionality. [Display omitted] •Dendrimers cause membrane thinning and structural disorder in lipid multilayers•Such effects depend on dendrimer size, surface chemistry, and dosage•Dendrimer clustering in multilayers depends on its addition method•Lipid multilayers provide a model system for studying dendrimer-membrane interactions•Such fundamental understanding has implications to nanotoxicity and drug delivery